Explaining Investment Dynamics: Empirical Evidence from German New Ventures - Habermann, Harald (Senate Hall, 2016)
So far, empirical evidence regarding investment patterns has focused almost entirely on established firms, and mainly in the manufacturing sector. No theory for investment has been empirically tested for new ventures. Using pooled panel data of 7,028 German new ventures, the present article documents the importance of zero-investment episodes and applies a cluster analysis to investigate if different investment patterns can be distinguished. The empirical results support the presence of both convex and non-convex components of adjustment costs, implying that both neoclassical and newer investment theories have practical validity. Keywords: convex adjustment costs, investment pattern, panel data
Keywords: convex adjustment costs|investment pattern|panel data